2011
DOI: 10.1021/jo201234f
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study on the Mechanism and Selectivity of C–H Bond Activation and Dehydrogenative Functionalization in the Synthesis of Rhazinilam

Abstract: The key platinum mediated C-H bond activation and functionalization steps in the synthesis of (-)-rhazinilam (Johnson, J. A.; Li, N.; Sames, D. J. Am. Chem. Soc. 2002, 124, 6900) were investigated using the M06 and B3LYP density functional approximation methods. This computational study reveals that ethyl group dehydrogenation begins with activation of a primary C-H bond in preference to a secondary C-H bond in an insertion/methane elimination pathway. The C-H activation step is found to be reversible while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Despite the modest yield and diastereoselectivity, together with the necessity using a stoichiometric amount of platinum, the success of this early example of CH activation was remarkable and highly instructive. A recent computational study based on density functional approximation methods reported by Ellis and Ess also provided further insights on the mechanism and selectivity of this CH activation/dehydrogenation reaction 10. Finally, isomerically pure imine 9 was subjected to transamination (NH 2 OH) followed by a palladium‐catalyzed macrolactamization11 and subsequent decarboxylation to complete the total synthesis of (−)‐rhazinilam ( 1 ).…”
Section: Recently Completed Total Syntheses Of Natural Products: Ch mentioning
confidence: 98%
“…Despite the modest yield and diastereoselectivity, together with the necessity using a stoichiometric amount of platinum, the success of this early example of CH activation was remarkable and highly instructive. A recent computational study based on density functional approximation methods reported by Ellis and Ess also provided further insights on the mechanism and selectivity of this CH activation/dehydrogenation reaction 10. Finally, isomerically pure imine 9 was subjected to transamination (NH 2 OH) followed by a palladium‐catalyzed macrolactamization11 and subsequent decarboxylation to complete the total synthesis of (−)‐rhazinilam ( 1 ).…”
Section: Recently Completed Total Syntheses Of Natural Products: Ch mentioning
confidence: 98%
“…This work was triggered by the following findings: (1) gold­(I) alkyl complexes are inert toward β-elimination reactions, and very detailed experimental evidence exists that accounts for this behavior; (2) on the contrary, gold­(III) has a d 8 electron configuration [valence isoelectronic with palladium­(II) and platinum­(II)], for which β-hydride eliminations are common; , (3) gold­(III)-catalyzed β-hydride eliminations have recently been suggested to occur in a gold complex featuring a highly strained cycloalkyl ligand . Guided by (1)–(3), we performed a detailed mechanistic study of β-hydride eliminations for a variety of gold­(I) and gold­(III) alkyl complexes to shed light onto the different mechanisms involving gold­(I) and gold­(III).…”
Section: Introductionmentioning
confidence: 99%